2011
DOI: 10.1111/j.1600-0838.2011.01368.x
|View full text |Cite
|
Sign up to set email alerts
|

Reducing errors benefits the field‐based learning of a fundamental movement skill in children

Abstract: Proficient fundamental movement skills (FMS) are believed to form the basis of more complex movement patterns in sports. This study examined the development of the FMS of overhand throwing in children through either an error-reduced (ER) or error-strewn (ES) training program. Students (n = 216), aged 8-12 years (M = 9.16, SD = 0.96), practiced overhand throwing in either a program that reduced errors during practice (ER) or one that was ES. ER program reduced errors by incrementally raising the task difficulty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
3
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(87 citation statements)
references
References 31 publications
6
74
3
4
Order By: Relevance
“…Focusing on overhand throwing, error-reduced learning has been shown to develop skills that are less dependent on cognitive resources [11,12]. The current findings deepen our understanding by providing insight into possible mechanisms that facilitate learning of movement pattern components, and development of skill mastery.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Focusing on overhand throwing, error-reduced learning has been shown to develop skills that are less dependent on cognitive resources [11,12]. The current findings deepen our understanding by providing insight into possible mechanisms that facilitate learning of movement pattern components, and development of skill mastery.…”
Section: Discussionmentioning
confidence: 61%
“…All procedures were reviewed and approved by the university institutional ethics review board, and had been reported in detail in two previously published papers [11,12].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Making hardly any errors hampers hypothesis testing about how movement performance can be optimized, and hence, little or no declarative knowledge will be accumulated. Error-minimizing learning has been successfully used to induce implicit motor learning in, for instance, golf putting and ball throwing, with the participants initially practicing at close distance to the hole or target but with the distance slowly being increased to enhance learning (Maxwell, Masters, Kerr & Weedon, 2001;Capio et al, 2013). A third, more contentious, method for implicit learning is learning with an external focus of attention.…”
Section: Methods For Implicit Motor Learningmentioning
confidence: 99%
“…In this respect, recent work by Capio and colleagues, which examined motor skill learning in children, is pertinent (for a recent overview, see Masters, van der Kamp & Capio, 2013). Capio, Poolton, Sit, Holmstrom, and Masters (2013), for example, reported that primary school children, who practiced throwing a beanbag to a target, showed larger gains in throwing form with implicit than explicit learning. Similarly, throwing accuracy also increased to a greater extent with implicit learning, but only for children with lower motor ability.…”
Section: Implicit and Explicit Motor Learningmentioning
confidence: 99%